Rankings games - Bruno S. Frey; Margit Osterloh (University of Zurich, Department of Economics, 2011)
Research rankings based on publications and citations today dominate governance of academia. Yet they have unintended side effects on individual scholars and academic institutions and can be counterproductive. They induce a substitution of the taste for science by a taste for publication. We suggest as alternatives careful selection and socialization of scholars, supplemented by periodic self-evaluations and awards. Neither should rankings be a basis for the distributions of funds within universities. Rather, qualified individual scholars should be supported by basic funds to be able to engage in new and unconventional research topics and methods.
Keywords: A10; D02; H83; L23; M50; 330; academic governance; rankings; motivation; selection; socialization; Ranking-Verfahren; Kritik; Leistungsmotivation; Sozialisation; Hochschulforschung